Advanced Shrinking Particle Model for Fluid-Reactive Solid Systems - Russo, Vincenzo; Grénman, Henrik; Cogliano, Tommaso; Tesser, Riccardo; Salmi, Tapio (Frontiers in Chemical Engineering, 2020)
In the present work, the Extended Shrinking Film Model (ESFM) was applied to a reversible reaction in which a solid dissolves and reacts with a component present into a liquid phase. The model considers the reactive solid dissolution in the liquid phase and the diminishing of its radius with the reaction time. Furthermore, the liquid film surrounding the particle, through which the liquid component diffuses to react with the dissolved solid, is considered radius-dependent; thus, the model is based on the mass balance equations derived on the solid surface, liquid bulk, and the liquid film. The model consists of two ODEs and a PDE, solved in the present paper using gPROMS ModelBuilder 4.0. It was demonstrated that the model can cover a wide range of operative conditions and shows high flexibility, allowing the application to several kinds of solid-fluid reactions such as esterification, gasification and steam cleaning for the removal of dangerous and polluting gases (CO2, SO2) from the main process stream and NO capture.